Genome analysis of novel Salmonella-infecting bacteriophage ?Sen-NF - RISKA AYU FEBRIANTI; ERLIA NARULITA; FADHILAH AYU SAVITRI; AGUNG HARIS WIDIANTO; HARDIAN SUSILO ADDY; ERMA SULISTYANINGSIH; KUSWATI KUSWATI; BINAR RAHMA UTAMI (Society for Indonesian Biodiversity, 2025)
Abstract. Febrianti RA, Narulita E, Savitri FA, Widianto AH, Addy HS, Sulistyaningsih E, Kuswati K, Utami BR. 2025. Genome analysis of novel Salmonella-infecting bacteriophage ?Sen-NF. Biodiversitas 26: 2011-2019. Genome mapping of bacteriophages that infect Salmonella is an important step in understanding the interactions between these pathogenic bacteria and viruses. Salmonella is one of the leading causes of food poisoning worldwide, with multiple serotypes that can cause serious infections in humans. This study aimed to identify and analyze bacteriophage genomes that can be used as therapeutic agents to control Salmonella infections. The study began with isolating bacteriophages from food samples, followed by morphological characterization, molecular and genomic analysis, and phylogenetics. The successfully isolated bacteriophage ?Sen-NF can only infect Salmonella enterica ser. Typhi, which has a diameter of ±1mm with a clear plaque. Bacteriophage ?Sen-NF, which infects Salmonella, is a linear double-stranded DNA virus with a genome size of 108,537 base pairs and a G+C content of 46.8%. Comparative genomic analysis revealed similarities with Myoviridae, such as ?SE24 and ?Sw2. Phylogenetic reconstruction showed a close evolutionary relationship with phages such as ?SE24 and ?Sw2. The results from this study are expected to make significant contributions to the development of new strategies to address food poisoning caused by Salmonella, as well as improve overall food safety.